TEMPORARY WORKER ALIENATION IN HIROKO OYAMADA’S NOVEL KOUJOU: ALIENASI PEKERJA TIDAK TETAP DALAM NOVEL KOUJOU KARYA HIROKO OYAMADA - Ni Luh Putu Ari Sulatri; Silvia Damayanti (Jurnal Kata, 2022)
Alienation causes workers to feel separated and alienated from the work they are doing so that work becomes a foreign and pseudo experience. The alienation experienced by workers can not only be found in everyday life but also becomes the theme of stories in literary works. One of the literary works with the theme of alienation is the novel Koujou by Hiroko Oyamada. This article examines the alienation of temporary workers in Koujou's novel. The temporary worker alienation is shown through the character of Yoshiko Ushimaya and the character of an older brother. The research problem is examined by the alienation theory of Karl Marx and the development of the alienation theory by Melvin Seeman. This research was conducted by applying a qualitative method. Based on the research results, it can be seen that in novel Koujou the alienation of temporary workers is described in the form of 1) alienation from self-potential; 2) alienation from products and production processes; 3) alienation from other workers; and 4) alienation from the meaning of work.